Development of triangular learning media based on adobe animate CC with ADDIE learning design - Nurfajar Wahyuliana; Dedek Andrian (International Journal of Trends in Mathematics Education Research, 2022)
This study aims to systematically develop technology-based interactive learning media to improve students' problem-solving and reasoning skills. This research is development research, namely the development of learning media based on Adobe Animate CC with ADDIE learning design on triangle material. The subjects of Adobe Animate CC learning media development are SMPN Bengkalis Regency students. The research instrument used is a validity assessment sheet for experts and practitioners. Data analysis uses descriptive statistics to see the percentage of answers from experts and practitioners and then compares them with standards of validity and practicality. The development results show that the created Adobe Animate CC has illustrations that can attract students' attention and interest (motivation) in learning mathematics. Experts and practitioners assess Adobe Animate CC learning media in the correct category with an average value of 81.55%. Experts and practitioners also estimate that Adobe Animate CC learning media is in the practical type, averaging 84.03%.